LINGUISTIC ANALYSIS OF LEGAL TERMINOLOGYIN ENGLISH AND UZBEK - Xasanbayeva Saodat A'zamjon qizi (TADQIQOTLAR, 2025)
Abstract: Legal terminology represents a specialized and highly conventionalized layer of vocabulary that ensures accuracy, consistency, and clarity in legal communication. This article provides a linguistic analysis of legal terminology in the English and Uzbek languages, with particular attention to its structural, semantic, and functional features. The study aims to identify both common and language-specific characteristics of legal terms that arise from differences in linguistic systems, legal traditions, and sociocultural contexts. The research employs descriptive and contrastive methods to examine morphological patterns, word-formation processes, and semantic properties of legal terms used in statutory texts, legal documents, and judicial discourse. Special emphasis is placed on terminological precision, polysemy, synonymy, and the issue of partial or non-equivalence between English and Uzbek legal terms. The analysis also addresses the pragmatic function of legal terminology, demonstrating how terms operate within institutional discourse to regulate meaning and minimize ambiguity. The findings reveal that while English and Uzbek legal terminologies share universal features such as formalization and stability, they differ significantly in their lexical composition, borrowing strategies, and syntactic realization. These differences often create challenges in legal interpretation and translation.